The Experience of Teenage 19 Years in Dealing with Ovary Cancer Stadium 1B with Understanding Spiritual: Qualitative Study - Wulan Anugrah Pauji Salam; Dian Ramawati; Endrian MJW (GLOBAL HEALTH SCIENCE GROUP, 2024)
Ovarian cancer has a physical and psychological impact. Experience in patients with ovarian cancer is very much needed, especially for those who have successfully gone through several stage so that they can continue to live and control their disease. Teenagers with cancer have complex problems. Adolescents with cancer who are at risk of experiencing developmental phase delays face limitations in carrying out their roles as adolescents. Objective: The purpose of this study was to determine the experience of 19-year-old adolescents in dealing with Stage 1B Ovarian Cancer with Spiritual Understanding. The case study approach uses a qualitative method, data collection using triangulation, individual in-depth interviews, documentation, and observation. Participants in this study amounted to one person. This research was conducted in August- September 2024. In the study of respondents’ experiences in dealing with stage 1B ovarian cancer, there were several discussions including self-acceptance with five stages, starting from denial, anger, bargaining, depression, acceptance, and spirituality that sufferers can take wisdom, the meaning of life and have hope for his future life, and believe that everything comes from God will return to God. Cancer sufferers experience all processes of self-acceptance, this cannot be separated from various social supports, their motivation, and their desire to heal themselves. So that, spiritually, Ovarian cancer sufferers can adapt to the situation and get a new meaning and angle of life.